"Refractivity-from-clutter" based on local empirical refractivity model*Project supported by the National Natural Science Foundation of China (Grant Nos. 41775027 and 41405025). (December 2018) - Zhao 赵, Xiaofeng 小峰
Abstract : Constructing sophisticated refractivity models is one of the key problems for the RFC (refractivity from clutter) technology. If prior knowledge of the local refractivity environment is available, more accurate parameterized model can be constructed from the statistical information, which in turn can be used to improve the quality of the local refractivity retrievals. The validity of this proposal was demonstrated by range-dependent refractivity profile inversions using the adjoint parabolic equation method to the Wallops'98 experimental data.